DESIGN THINKING IN WRITTEN COMMUNICATION - Borissova, Lalka; Borissova, Lalka (Revista Inclusiones, 2020)
Communication is one of the most important and useful processes in modern society. Good communication is essential for the mutual understanding between the parties involved in the communication process. It can only be effective if the parties are able to get over the mistrust and scepticism that are characteristic for the business relationships today. They must build relations based on trust and mutual respect - an important factor for the long-term success of the organization as well as for their career and personal development. The success of on organization depends on the effectiveness of its business communication (written and oral) in terms of achievement of the desired reaction or outcome. The information exchanged in the process of communication should not only be useful, but also make people feel good as members of their team, department, or organization. The timely exchange of information ensures that accurate and timely decisions are made, things are done better, and people are more motivated. The process of communication (sending, receiving, and interpreting the message) is the ability of people to understand and be understood while communicativeness is their ability to organize and formulate their ideas orally and in writing. The subject of this article is written communication and the requirements for composing different documents in terms of their type, style, and purpose. I believe that design thinking, i.e. the author’s ability to use a great variety of design styles and text formats to produce comprehensive texts, plays an essential role in this process.